European constitutionalism as the metatheory of the construction of legal and political reality and the challenges for its development - Jolanta Bieliauskaitė; Vytautas Šlapkauskas (DANUBE: Law, Economics and Social Issues Review, 2016)
The latter European crisis reveals the fact that traditional agreements between governments of the Member States and supranational political and legal institutions of the European Union are not sufficient for the maintenance of European Union stability and integrity. Therefore, the political and legal sustainability of the European Union requires a certain metatheory as a methodology, which could essentially contribute to the coherent construction, interpretation and assessment of theoretical and practical issues of the European Union's legal and political reality. This paper aims to explore two main questions: What is constitutionalism as a legal-political metatheory? What challenges are faced by this theory while addressing the specific EU legal-political reality construction problems? The results of the research reveal that constitutionalism as a metatheory is constituted by principles and values, which provide ideological support for the development of the nation, and performs a methodological function in the construction of legal and political reality. However, the EU's political elite still seeks to legitimize constitutionalism as a political action theory, which, accordingly, legitimizes the respective legal policies it pursues. This process dangerously increases the gap between the EU's political elite and the societies of its Member States.
Keywords: 330; The European Union; Constitutionalism; Liberal Democracy; European Integration; Legal Metatheory